The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/8897881
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Teach-Back Method on Knowledge, Performance, Readmission, and Quality of Life in Heart Failure Patients

Abstract: Background. Among chronic diseases, heart failure has always been a serious challenge imposing high costs on health systems and societies. Therefore, nurses should adopt new educational strategies to improve self-care behaviors and reduce the readmissions in heart failure patients. This study aimed to determine the effect of the teach-back method on knowledge, performance, readmission, and quality of life in these patients. Methods. This clinical trial was conducted in patients with heart failure (n = 70) hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
1
8
0
1
Order By: Relevance
“…Some of the nurses in the current study used the teach-back education method to reinforce self-care advice in the patients. Evidence supports the use of the teach-back method to maximize the disease understanding of people with chronic disease and promote their knowledge, adherence, self-efficacy, and self-care skills [ 52 , 53 ]. Use of the teach-back method, in addition to building caring relationship and providing continuity, can be the key to migrant patients’ effective adaptation to self-care management.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the nurses in the current study used the teach-back education method to reinforce self-care advice in the patients. Evidence supports the use of the teach-back method to maximize the disease understanding of people with chronic disease and promote their knowledge, adherence, self-efficacy, and self-care skills [ 52 , 53 ]. Use of the teach-back method, in addition to building caring relationship and providing continuity, can be the key to migrant patients’ effective adaptation to self-care management.…”
Section: Discussionmentioning
confidence: 99%
“…Also, study of Kola et al show teach-back method increasing the level of knowledge led to promote of self-care behaviors, patient-caregiver self-reporting and quality of life in these patients [ 30 ]. In addition, Tran et al showed that teach-back education caused a longer retention of the information learned and improved the effectiveness of health outcomes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported that teach-back education methods that offer face-to-face education about the signs and symptoms of heart failure, diet, medication, and exercise can positively affect heart failure patients’ QoL and health literacy as routine discharge educations. [ 42 ]…”
Section: Discussionmentioning
confidence: 99%